PENERAPAN METODE SAW DALAM SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JURUSAN PADA SEKOLAH MENENGAH ATAS NEGERI 8 SELUMA - Melisa Elistri; Jusuf Wahyudi; Reno Supardi (Jurnal Media Infotama, 2014)
This writing aim to to make system supporter of decision of Election of majors at school use visual microsoft of basic 6.0. research done by Senior High School (SMA) Country 8 Seluma. Method weared in data collecting Observation, interview, and Study Book. Lifted a case which searching best alternative pursuant to criterions which have been deter-mined by using method of SAW (Simple Additif Weighting) to do calculation. From solution and result can be concluded that by using computerization, system supporter of this decision can be exploited as one of consideration in intake a[n decision by go to school in taking decision of student majors.Keyword: System Supporter of Decision, SAW